Effect of active Gurney flaps on overall helicopter flight envelope. (7th June 2016) - Pastrikakis, V.A.; Steijl, R.; Barakos, G.N.
ABSTRACT: This paper presents a study of the W3-Sokol main rotor equipped with Gurney flaps. The effect of the active Gurney is tested at low and high forward flight speeds to draw conclusions about the potential enhancement of the rotorcraft performance for the whole flight envelope. The effect of the flap on the trimming and handling of a full helicopter is also investigated. Fluid and structure dynamics were coupled in all cases, and the rotor was trimmed at different thrust coefficients. The Gurney proved to be efficient at medium to high advance ratios, where the power requirements of the rotor were decreased by up to 3.3%. However, the 1/rev actuation of the flap might be an issue for the trimming and handling of the helicopter. The current study builds on the idea that any active mechanism operating on a rotor could alter the dynamics and the handling of the helicopter. A closed loop actuation of the Gurney flap was put forward based on a pressure divergence criterion, and it led to further enhancement of the aerodynamic performance. Next, a generic light utility helicopter was built using 2D aerodynamics of the main aerofoil section of the W3 Sokol blade along with a robust controller, and the response of the rotorcraft to control inputs was tested. This analysis proved that the 1/Rev actuation of the Gurney did not alter the handling qualities of the helicopter, and as a result, it can be implemented as a flow control mechanism for aerodynamic enhancement and retreating blade stall alleviation.